Understanding Charity: The Market Model - Evidence from Malaysia - Mohd Arshad, Mohd Nahar (International Journal of Economics, Management and Accounting, 2026)
This study theorizes a charity market model. Using the model, measure of necessities (daruriyyat) and charity equilibrium have been identified. The developed model offers a practical tool for policymakers to formulate policies regarding poverty eradication, minimum wage, and welfare programs. The proposed model is novel since it incorporates the third-sector economy, where charity (zakat and voluntary charity) is instrumental in empowering society to meet its needs. This study constructs and estimates a theoretical demand and supply model of cash charity, examining determinants such as income, age, education, gender, marital status, household size, location, and job types. The estimations identify the market clearing level of charity, offering a practical approach to determine the threshold level of income for basic needs fulfilment.